Optimizing Regional Development Policies through the RT Keren Program to Support Community Empowerment (Study in Blitar City) - Ahmad Suryaningrat; Sarwono Sarwono; Firda Hidayati (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
This study aims to identify and analyze the optimization of regional development policies through the RT Keren program to support community empowerment in Blitar City. This optimization is related to applying transformative ideas and answers to sustainable development programs or SDGs. The research method used is descriptive with a qualitative approach. The results show that government development policies involving community participation through a community empowerment approach positively impact people's lives by providing training and improving the community's economy. Development policy through the minor structure in the region, namely the RT, is a form of policy that impacts all elements of society, such as improving the quality of community life through community groups (POKMAS). Hence, this research will present empirical evidence about the indicators of transformative leadership within community empowerment initiatives while also examining the efficacy of regional development policies outlined in the vision of Blitar City, specifically the Blitar Keren initiative. One notable manifestation of this vision is the RT Keren program.